The PCR-based detection and identification of the parasites causing human cutaneous leishmaniasis in the Iranian city of Ahvaz - Ghasemian, M (Maney Publishing, 2011)
In Iran, Leishmania major or L. tropica cause almost all of the human cutaneous leishmaniasis (CL). Unfortunately, the detection methods frequently used for CL (the microscopical examination of direct smears or the culture of biopsies) are not very sensitive and the Leishmania species causing each case of CL in Iran is usually only tentatively identified from extrinsic factors, such as the case’s clinical manifestations and region of residence. Recently, however, a nested PCR that targets the parasites’ kinetoplast DNA has been used in the city of Ahvaz (the capital of the province of Khouzestan, in south–western Iran) to confirm the microscopical diagnosis of CL and to identify the causative parasites, to species level. Smears from the lesions on 100 suspected cases of CL were fixed, stained with Wright’s eosin–methylene blue, and checked for amastigotes under a light microscope. Scrapings from the same smears were then tested for leishmanial DNA, using a nested PCR that allows the DNA from L. tropica to be identified and distinguished from that of L. major. The 100 smears investigated were all found amastigote-positive by microscopy and PCR-positive for either L. major DNA (97 smears) or L. tropica DNA (three smears). The predominant species causing CL in Ahvaz is therefore L. major.